Peran Koperasi sebagai Badan Usaha dalam Meningkatkan Perekonomian Rakyat - Gustina Sari; Theresia Enjel Octavia Sihombing; Khairani Alawiyah Matondang; Feryanto Nababan (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
Cooperatives play a crucial role as business entities in enhancing the people's economy in Indonesia. Rooted in the principles of kinship and mutual cooperation, cooperatives aim to improve the welfare of their members and society at large, rather than merely pursuing profit. This study employs a descriptive analysis method to examine the role of cooperatives as a pillar of the people's economy, focusing on their contributions to microeconomic empowerment, job creation, and strengthening community purchasing power. The findings indicate that cooperatives significantly contribute to local economic growth, particularly through synergy with MSMEs (Micro, Small, and Medium Enterprises), as well as by providing members with access to capital and training. However, challenges such as weak management, low financial literacy, and inadequate technological adaptation still hinder the optimization of cooperatives' roles. On the other hand, sharia cooperatives also emphasize social functions based on principles of justice and social responsibility. To enhance the contribution of cooperatives, institutional strengthening, professional management, and regulatory support from the government are required. Thus, cooperatives remain relevant as instruments for inclusive and sustainable economic development in Indonesia.